(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
A Dense Wavelength Division Multiplexing (DWDM) system is a vital component in the optical network for the transmission of high data over a long distance. However, the non-linear effect of Four-Wave Mixing (FWM), one of the critical non-linear effects, limits the channel capacity and the amount of data that the DWDM system transmits. Intensity Modulation formats and Channel Shuffling algorithms being used to overcome the impact of FWM in DWDM are unable to sufficiently suppress the FWM effect due to limited capacity. This research, therefore, examined the mitigation of the FWM effect in the DWDM system using Dual Polarization Quadrature Phase Shift Keying (DP-QPSK) and channel arrangement. The DP-QPSK was designed and implemented using 100 GHz for both Equal Space Channel Allocation (ESCA) and Unequal Space Channel Allocation (USCA). It was analysed on a 64-channel DWDM system operating at 100 Gbps capacity over a transmission distance of 1000 km. The DP-QPSK-based ESCA and USCA techniques were simulated using OptiSystem 17 simulation software and Python for data analysis. The performance of the system was evaluated using bit error rate (BER), optical signal-to-noise ratio (OSNR) and Electrical Constellation Diagram. Validation was done with other advanced modulation formats: Quadrature Phase Shift Keying (QPSK) and Differential-Quadrature Phase Shift Keying (D-QPSK). The DWDM system using DP-QPSK gave better performance due to the highest OSNR and BER values obtained when compared with ESCA-based QPSK and D-QPSK techniques. The technique can be used to suppress the effect of FWM in optical communication systems.